Crafting Voices, Shaping Thought: Integrating Scaffolding Strategies to Foster Critical Literacy in Selected Young EFL Writers - Susilowaty, Susilowaty; Setyarini, Sri; Gustine, Gin Gin (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2025)
In response to the growing need for critical literacy in adolescent English as a Foreign Language (EFL) education, this study investigates how scaffolding techniques support junior high school students in navigating complex social texts and expressing critical perspectives through writing. While the concept of critical literacy is well-established, its classroom application in Indonesian EFL contexts remains limited, particularly with younger learners and genre-based instruction.This single case study employed a qualitative approach, incorporating classroom observations and three rounds of semi-structured interviews to examine how an experienced EFL teacher in a South Jakarta junior high school implemented scaffolding strategies during a biography writing project on Vincent van Gogh. The research was guided by Lewison et al.’s four dimensions of critical literacy, alongside established models of instructional scaffolding. The analysis identified four key scaffolding types: procedural scaffolding supported students in organizing content and mastering genre conventions; motivational scaffolding sustained engagement and encouraged creative risk-taking; conceptual scaffolding introduced abstract themes such as justice and identity; and metacognitive scaffolding facilitated students’ reflection on texts and their own perspectives. Among these, metacognitive scaffolding emerged as the most impactful, enabling students to examine diverse viewpoints and connect personal insights with broader sociopolitical issues. These findings underscore the importance of responsive, differentiated instruction in fostering critical engagement among adolescent EFL learners. The study contributes a pedagogically grounded model that integrates language development with reflective inquiry, offering practical implications for educators and curriculum designers aiming to cultivate social awareness and ethical reasoning in language classrooms.